2014
DOI: 10.1002/dev.21225
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in visual contour integration: Implications for physiology from psychophysics

Abstract: Visual contour detection is enhanced by grouping principles, such as proximity and collinearity, which appear to rely on horizontal connectivity in visual cortex. Previous experiments suggest that children require greater proximity to detect contours and that, unlike adults, collinearity does not compensate for their proximity limitation. Over two experiments we test whether closure, a global property known to facilitate contour detection, compensates for this limitation. Adults and children (3-9 years old) pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 60 publications
2
26
0
Order By: Relevance
“…To date, few studies have explored the development of such a closure mechanism across childhood (Gerhardstein et al, 2004; Hadad and Kimchi, 2006; Baker et al, 2008; Hadad et al, 2010a; Hipp et al, 2014). Using a mobile conjugate reinforcement procedure, Gerhardstein et al (2004) found that unlike adults, 3- to 4-month-old infants show no evidence of a closure superiority effect when detecting contours embedded in noise regardless of noise density; manipulation of contour type (open or closed) did not affect sensitivity to the contour at this age.…”
Section: Path To Object Perceptionmentioning
confidence: 99%
“…To date, few studies have explored the development of such a closure mechanism across childhood (Gerhardstein et al, 2004; Hadad and Kimchi, 2006; Baker et al, 2008; Hadad et al, 2010a; Hipp et al, 2014). Using a mobile conjugate reinforcement procedure, Gerhardstein et al (2004) found that unlike adults, 3- to 4-month-old infants show no evidence of a closure superiority effect when detecting contours embedded in noise regardless of noise density; manipulation of contour type (open or closed) did not affect sensitivity to the contour at this age.…”
Section: Path To Object Perceptionmentioning
confidence: 99%
“…Kovacs (2000) demonstrated, for example, that children's perceptual organization abilities continue to mature during middle childhood. Contour integration specifically appears to develop slowly (Hipp et al, 2014;Hadad, Maurer & Lewis, 2010), which may also point to a more general failure of spatial integration affecting performance in some tasks positively (children are less sensitive than adults to the Ebbinghaus illusion, (Doherty et al, 2010), while proving sub-optimal in other settings (Jeon et al 2010). Considered together, these results suggest that children may have reduced sensitivity to the differences between stimuli that match the statistical properties of natural scenes and those that don't.…”
Section: Introductionmentioning
confidence: 92%
“…Behavioral evidence supporting mechanisms of contour detection suggest that this function is present in the early stages of development (Field et al, 1993;Kovács et al, 1999;Hipp et al, 2014;Taylor et al, 2014), however, full maturation of this function requires years of visual experience. Kovács et al (1999) reported that children younger than 3 years of age were unable to identify a coherent contour defined by a circular ring of gabor patches embedded in noise, and their ability to perform the task improved into their teenage years.…”
Section: Development Of Contour Integration Perceptionmentioning
confidence: 99%